The Effect of Product and Price on Purchasing Decisions of Unilever Products at CV Kita Beauty Pontianak - Jacinda Malva Liya; Helman Fachri (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
Competition in the Fast Moving Consumer Goods (FMCG) industry and the cosmetic retail sector in Pontianak City encourages consumers to be increasingly selective in making purchasing decisions, particularly by considering product quality and price suitability. This condition is relevant for CV Kita Beauty Pontianak as a cosmetic retailer that serves as one of the distribution channels for Unilever products. The research problem of this study is whether product and price influence purchasing decisions of Unilever products at CV Kita Beauty Pontianak, both partially and simultaneously. This study aims to analyze the effect of product and price on purchasing decisions of Unilever products at CV Kita Beauty Pontianak. The method used is associative research with a quantitative approach. Primary data were collected through closed questionnaires and interviews, while secondary data were obtained from company documents. The research sample consisted of 100 respondents using a purposive sampling technique, and data analysis was conducted using multiple linear regression accompanied by validity tests, reliability tests, and classical assumption tests (normality, linearity, and multicollinearity). The results show that the research instruments are valid and reliable and that the model meets classical assumptions. Partially, product has a positive and significant effect on purchasing decisions (β = 0.374; t = 4.356; p < 0.05) and price has a positive and significant effect on purchasing decisions (β = 0.268; t = 3.408; p < 0.05). Simultaneously, product and price have a significant effect on purchasing decisions (F = 30.107; p < 0.05) with a coefficient of determination (R²) of 0.485, indicating that 48.5% of the variation in purchasing decisions is explained by product and price.